YASHIL IQTISODIYOTNI RIVOJLANTIRISHDA MOLIYAVIY HISOBOTNING XALQARO STANDARTLARINING XORIJ TAJRIBALARI (Marketing Journal, 2025)
The article discusses the r ole of international financial reporting standards (IFRS, GRI, TCFD, ESG) in the development of a green economy and how they are used in the experience of foreign countries. In particular, the approaches of countries such as the European Union, Great Brita in, the USA, Japan and South Korea are analyzed, and 145 the effectiveness of integrating environmental and social issues into financial reporting is shown. The advantages, practical possibilities and proposed directions of applying these standards in the national context for Uzbekistan are substantiated. The re sults of the study show that it is possible to increase financial transparency, attract green investments and strengthen corporate social responsibility through the gradual
Keywords: Green economy; financial reporting; international standards; IFRS; GRI; TCFD; ESG; sustainability reports; foreign experience; green investments; environmental information; economy of Uzbekistan